COMMUNICATIVE COMPETENCE AS THE MAIN GOAL OF TEACHING ENGLISH AS A SECOND FOREIGN LANGUAGE - D.T.Rahmonova (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Abstract. The relevance of the studying on a multilingual basis as a basic component of in-depth language education is determined, first of all, by the general global trend towards integration in the economic, cultural and political spheres, which in the educational sphere determines the tendency towards the integration of subject knowledge, a focus on understanding the holistic picture of the world [1]. The purpose of the article is to theoretically explain the concept of multilingualism or multilingualism, identify the features of multilingual education, study modern methods in multilingual education, as well as the practical development of one’s own methodology for teaching English as a second foreign language.